COLABORATIVE GOVERNANCE TRIPLE HELIX DALAM PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MEWUJUDKAN VISI INDONESIA EMAS 2045 - Dwi Putri Yuliani; Aldi Gumuruh Wicaksono; Elsawuri Raya Asrijati (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2026)
The main challenge in the development of human resources (HR) in Indonesia is the low quality of education. The purpose of this research is to find out the policy management and strategies of Higher Education in realizing the Golden Indonesia Vision 2045 based on Government Regulation (PP) Number 60 of 1999. The research method uses a qualitative method with a literature review approach (literature study). The results of the study show that: Higher Education Policy Management and Strategy to realize a Golden Indonesia 2045 is the application of technology-based education management and digital literacy to create human resources who are able to compete at the national and international levels; optimizing the link and mach policy to strengthen the role of universities and the industrial sector as well as collaborative governance triple helix; and improving access to education in remote areas with the opening of public schools and satellite campuses.